Collecting Malware in Swiss German University with Low Energy and Cost Computer - Marcello, Mario (Swiss German University, 2018)
The malware spreads massively in Indonesia. The security in Information Technology doesn’t seem to become a top priority for Indonesian. The use of pirated software is still high, although it is the biggest threat and entrance for the malwares to attacks. This paper shows how to collect a spreading malware in a system to know the malware trends that exist. So, the owner may know the malware trends inside his system and he can countermeasure the attacks. To collect the malwares, I use the Dionaea, the honeypot to collect malware and implement it to Raspberry Pi. Raspberry Pi is a small, low cost and low energy consumption computer. By using Raspberry Pi to collect malware, we can minimize budget, save the energy and space.